Fluorescence In Vivo Endomicroscopy Part 2: Applications of High-Resolution, 3-Dimensional Confocal Laser Endomicroscopy. (May 2021) - Rangrez, Mohammedayaz; Bussau, Lindsay; Ifrit, Kishwar; Preul, Mark C.; Delaney, Peter
Abstract : Abstract: Fluorescence in vivo endomicroscopy (FIVE) is a state-of-the-art endoscopy technique used to image tissue interactions and molecular events in a cell. In Part 1 of this series, the history, types of confocal laser endomicroscopy (CLE), and limitations of the technology were discussed. In Part 2 of the series, we describe several applications of FIVE technology, including advances in cancer, gastrointestinal, liver, rectal mucosal barrier function, acute lung injury, and brain imaging. Future perspectives for the technology are also presented.